Pengaruh Gaya Kepemimpinan Transformasional Dan Kepuasan Kerja Terhadap Kinerja Karyawan Bagian Perkantoran PTPN III Rantauprapat - Nisa Anindita; Sjahril Effendy; Syafruddin Ritonga (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research was conducted to see the effect of transformational leadership style and job satisfaction on the performance of employees at the office of PTPN III Rantauprapat.The hypothesis proposed is the influence of transformational leadership and job satisfaction on the performance of employees of the officer at PTPN III Rantauprapat. The sample in this study amounted to 105 people from a population of 105 people. Sampling technique is to use total sampling. The data collection method is a Likert scale of transformational leadership, job satisfaction, and employee performance. Data analysis used multiple regression linear analysis model. The results of this study are: 1. There is a significant influence between transformational leadership on employee performance. This is indicated by the t-count value of transformational leadership of 4.799 > t table of 1.984 and the Sig value of 0.000 <0.025. 2. There is a significant influence between job satisfaction on employee performance. This is indicated by the t-count coefficient of job satisfaction, which is 7.709 > t table 1.984 and the Sig value is 0.000 <0.025. 3. There is a significant influence between transformational leadership and job satisfaction on employee performance. This is indicated by the calculated F value of 66,235 > F table 19,487 and the significance value of 0.000 with p value < 0.05. Based on the results of this study, the proposed hypothesis is accepted.